Use of microaxial flow pumps in adolescentsCentral MessagePerspective - Lauren E. Parker, BS; Douglas M. Overbey, MD; Lillian Kang, MD; Cathlyn K. Medina, BA; Leonie M. Kurzlechner, BS; Ziv Beckerman, MD; Nicholas D. Andersen, MD; Jacob N. Schroder, MD; Joseph Turek, MD, PhD, MBA (JTCVS Techniques)
Objectives: The Impella 5.5 has been successfully used in the adult population; however, safety and efficacy data in patients aged less than 18 years are limited. Methods: Six pediatric patients, aged 13 to 16 years and weighing 45 to 113 kg, underwent axillary artery graft placement and attempted placement of the Impella 5.5 device at our institution between August 2020 and March 2023. Results: Indications for implantation were heart failure secondary to myocarditis (2), rejection of prior orthotopic heart transplant, idiopathic dilated cardiomyopathy (2), and heart failure after transposition of the great arteries repair. Placement was unsuccessful in a 13.8-year-old female patient due to prohibitively acute angulation of the right subclavian artery, and venoarterial extracorporeal membrane oxygenation cannulation was performed via the axillary graft. In 5 patients with successful Impella 5.5 placement, median duration of support was 13.5 days (range, 7-42 days). One experienced cardiac arrest secondary to coagulation-associated device failure, requiring temporary HeartMate3 implantation. Four patients were bridged to transplant; 3 patients received a transplant directly from Impella 5.5, and 1 patient received a transplant after HeartMate3. The final patient received the HeartMate3 on Impella day 42 and is awaiting transplant. Conclusions: Although exact size cutoffs and anatomy are still being determined, our experience provides a framework for use of the Impella 5.5 in adolescents.